Embodied viewing and Degas's Little Dancer Aged Fourteen: a multi-disciplinary experiment in eye-tracking and motion capture. (2nd September 2019) - Wiseman, Boris; Carusi, Annamaria; Briggs, Eloise; Poyntz, Sarah; Pelowski, Matthew; Alcock, Lisa; Mazzà, Claudia
ABSTRACT: This paper presents a cross-disciplinary project based on an experiment in eye-tracking and motion capture (Sainsbury's Centre for Visual Arts), which aimed to study viewers' movements around an iconic sculpture: Edgar Degas's Little Dancer Aged Fourteen . The experiment studies how viewers respond to this three-dimensional artwork not only by looking at it but also through their own bodily reactions to it, such as by unconsciously mimicking a represented attitude or gesture. We compared two groups of viewers: classically trained dancers and non-dancers. Our hypothesis was that the skills and embodied experiences of the dancers would alter the ways in which they engage bodily with the work compared to the non-dancers. Our underlying research question was: how are vision and the body interlinked in esthetic and kinesthetic experience? This paper does not give results, which are forthcoming. It focuses on methodology and provides a commentary on the design and development of the interdisciplinary collaboration behind the project. It explores an interdisciplinary collaboration that bridges the humanities and experimental sciences and asks how being confronted with unfamiliar methodologies forces researchers in a given field to critically self-examine the limits and presuppositions of their practices.